Comparative Analysis of Modified Altman Z-Score and Springate Models in Predicting Financial Distress: Evidence from Property Companies Listed on the Indonesia Stock Exchange (2018-2022) - Muhammad Ilham; Yusuf Asyahri; Faqih El Wafa; Syaugi Syaugi; Alfisah Alfisah (https://jurnal.binamandiri.ac.id/, 2026)
This research aims to analyze differences in bankruptcy prediction results using two methods, the Altman Z-Score and Springate, for property companies listed on the Indonesian Stock Exchange during 2018-2022. This type of research is both quantitative and descriptive. Purposive sampling was used; four companies were selected according to the criteria, and those that regularly published their financial reports in 2018-2022 were included as samples in this research. The results show that the Modified Altman Z-Score provides a more realistic assessment of gradual financial deterioration. At the same time, the Springate model is overly sensitive to short-term declines in profitability and tends to overclassify firms as financially distressed during the pandemic. The findings suggest that the Modified Altman Z-Score is a more suitable early warning tool for financial distress in the property sector, with important implications for monitoring working capital and EBIT as key indicators of financial resilience.